Analisis Kerentanan SQL Injection Menggunakan SQLMap pada Kali Linux - Kurniawan, Nanda Dwi; Firdaus, Azmi Maulana; Abriansah, Fausta Rizky; Ferdian, Praditya Rendi; Susanto, Susanto (Universitas Indraprasta PGRI Jakarta, 2025)
SQL injection is one of the serious threats in website security that can jeopardize the integrity of the database. This research focuses on using Sqlmap integrated in Kali Linux operating system to analyze website database vulnerability. Kali Linux was chosen because it is a Linux distribution specifically designed for penetration testing and has been equipped with various cybersecurity tools, including Sqlmap as a reliable open-source framework to detect and analyze SQL injection vulnerabilities automatically. The main objective of the research is to develop a systematic methodology in analyzing website database vulnerabilities through SQL injection techniques. The methodology includes the installation and configuration of Sqlmap on Kali Linux, implementation of penetration testing, and comprehensive analysis of the vulnerability findings. This research also emphasizes the importance of implementing security mechanisms and mitigation strategies to protect data integrity from SQL injection attacks. The results of this research are expected to contribute to the development of better cybersecurity practice.